2010
DOI: 10.1136/tc.2009.032805
|View full text |Cite
|
Sign up to set email alerts
|

Human electroencephalography and the tobacco industry: a review of internal documents

Abstract: Tobacco manufacturers successfully developed objective, EEG-based techniques to evaluate the influence of product characteristics on acceptance and use. Internal results suggest that complex interactions between pharmacological, sensory and behavioural factors mediate the brain changes that occur with smoking. These findings have implications for current proposals regarding the regulation of tobacco products and argue for the incorporation of objective measures of product effects when evaluating the health ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Numerous tobacco-related diseases and premature deaths are consequences of persistent tobacco exposure (Panzano, Wayne, Pickworth, & Connolly, 2010). The disease burden resulting from SHS exposure includes cardiovascular disease, lung cancer, respiratory disease, breast cancer, chronic obstructive pulmonary disease (COPD), tuberculosis, as well as developmental defects in children and fetuses (Oberg, Jaakkola, Woodward, Peruga, & Pruss-Ustun, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous tobacco-related diseases and premature deaths are consequences of persistent tobacco exposure (Panzano, Wayne, Pickworth, & Connolly, 2010). The disease burden resulting from SHS exposure includes cardiovascular disease, lung cancer, respiratory disease, breast cancer, chronic obstructive pulmonary disease (COPD), tuberculosis, as well as developmental defects in children and fetuses (Oberg, Jaakkola, Woodward, Peruga, & Pruss-Ustun, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Similarly, tobacco companies have utilized neuromarketing strategies to evaluate product characteristics and appeal of advertising campaigns. [28][29][30] This utilization, in combination with the unregulated nature of online tobacco marketing, may lead adolescents to passively engage with online tobacco marketing through their routine use of the Internet, though they may not consciously recall this engagement. The recent repeal of net neutrality (a principle by which Internet service providers treat all Internet traffic equally) 31,32 may exacerbate this problem by enabling tobacco companies to purchase Internet ads more effectively and target those ads more directly.…”
Section: Discussionmentioning
confidence: 99%
“…The addictiveness of tobacco products is linked to the dose and speed of nicotine delivery and it has been suggested that tobacco products can be made less addictive and possibly ‘non-addictive’ by reducing the nicotine content of cigarettes (ie, the amount of nicotine contained in the tobacco itself) 24. This strategy merits further research as tobacco companies have explored nicotine thresholds,25 and it may be an easier strategy to adopt than one aimed at reducing harm. However, we believe that there is currently insufficient evidence and experience with this approach given the substantial risks of adopting such a strategy: concerns remain about compensatory smoking; nicotine has been shown to exert effects at relatively low levels and there is likely to be individual variability in any nicotine ‘threshold’ level of addictiveness; and the lure of black market cigarettes having higher nicotine levels 24 26 27.…”
Section: Types Of Regulationmentioning
confidence: 99%